Redesain UI/UX Sistem Pemesanan Menu Menggunakan Metode Design Thinking - Sharazita Dyah Anggita; Zilva Nur Fajrul Falaq; Irma Rofni Wulandari; Anna Baita (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to design and develop the user interface (UI) and user experience (UX) of a web-based menu ordering system using the Design Thinking method. The development process includes the stages of empathize, define, ideate, prototype, and testing to ensure that the final solution aligns with user needs. The prototype was further refined into a frontend design emphasizing ease of navigation, clarity of information, and efficiency of the ordering flow. Usability evaluation was conducted using the System Usability Scale (SUS). The assessment results show a SUS score of 70, in the Good category in the adjective rating. This indicates that the system design is acceptable to users and can be further developed into a complete frontend implementation. Overall, the Design Thinking approach proved effective in producing an intuitive, functional, and user-centered interface design.